Pengaruh Perceived ease Of Use, Perceived Usefulness dan Trust Terhadap Intention To use Aplikasi Access By KAI - Intan Ardiyanti; Wheny Khristianto; Ika Sisbintari (Universitas Diponegoro, 2026)
Abstract: The large number of KAI passenger who are entering the digital word, therefore customer intention is needed to be able to use the Access by KAI application. The purpose of this study was to determine the effect of perceived ease of use, perceived usefulness and trust on the intention to use the Access by KAI application. This type of research method uses a quantitative approach with a population of Access by KAI application users in Jember Regency with a sample of 130 respondents determined by the Ferdinand formula. The sampling technique in this study used non-probability sampling because there was no accurate data on the number of users of the Access by KAI application feature in Jember Regency. The data analysis method used multiple linear regression analysis, ease of data proscessing with IBM SPSS 26 software. The results of this study indicate that the influence of perceive ease of use, perceived usefulness and trust has a significant effect on the intention to use the Access by KAI application.Abstraksi: Banyaknya penumpang KAI yang memasuki dunia digital, oleh karena itu diperlukan intention pelanggan untuk dapat menggunakan aplikasi Access by KAI. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh perceived ease of use, perceived usefulness dan trust terhadap intention to use aplikasi Access by KAI. Jenis metode penelitian menggunakan pendekatan kuantitatif dengan populasi oleh pengguna aplikasi Access by KAI di Kabupaten Jember dengan sampel sebanyak 130 responden yang ditentukan dengan rumus Ferdinand. Teknik pengambilan sampel pada penelitian ini menggunakan non-probability sampling karena belum adanya data akurat mengenai jumlah pengguna fitur aplikasi Access by KAI di Kabupaten Jember. Metode analisis data menggunakan analisis regresi linier berganda, kemudahan pengolahan data dengan software IBM SPSS 26. Hasil penelitian ini menunjukkan bahwa pengaruh perceived ease of use, perceived usefulness dan trust berpengaruh signifikan terhadap intention to use aplikasi Access by KAI.